ALK Immunohistochemistry for ALK Gene Rearrangement Screening in Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis. Issue 4 (October 2016) - Pyo, Jung-Soo; Kang, Guhyun; Sohn, Jin Hee
Introduction: The aim of this study was to investigate the diagnostic accuracy of anaplastic lymphoma kinase (ALK) immunohistochemistry (IHC) for ALK gene rearrangement in non-small cell lung cancer (NSCLC) through systematic review, meta-analysis and diagnostic test accuracy review. Methods: The current study included 11, 806 NSCLC cases in 42 eligible studies. We performed concordance analyses between ALK IHC and fluorescence in situ hybridization (FISH). The diagnostic accuracy of ALK IHC was analyzed based on ALK IHC criteria and antibodies. Results: The overall ALK IHC results were positive in 13.2%. The overall concordance rate between ALK IHC and FISH was 0.950 (95% confidence interval [CI], 0.927-0.966). In the ALK IHC-positive and negative groups, the concordance rates were 0.805 (95% CI 0.733-0.861) and 0.985 (95% CI 0.978-0.990), respectively. The ALK FISH-positive rates were 0.009 (95% CI 0.004-0.023), 0.378 (95% CI 0.217-0.572), 0.628 (95% CI 0.420-0.796) and 0.900 (95% CI 0.840-0.939) in the ALK IHC 0, 1+, 2+ and 3+ groups, respectively. In diagnostic test accuracy review for ALK IHC, the pooled sensitivity and specificity were 0.92 (95% CI 0.89-0.94) and 0.91 (95% CI 0.90-0.91), respectively. The diagnostic odds ratio and the area under the curve on the summary receiver operating characteristic curve were 266.56 (95% CI 110.83-641.14) and 0.983, respectively. Conclusions: Our results suggested that ALK IHC equivocal (score 1+ and 2+) cases should not be considered as IHC-negative in screening for ALK gene rearrangement. Additional detailed criteria for ALK IHC equivocal cases are necessary to determine how to best apply this approach in daily practice.